2009
DOI: 10.1080/03601230902997733
|View full text |Cite
|
Sign up to set email alerts
|

Potential exposure of children and adults to cypermethrin following use of indoor insecticide foggers

Abstract: The magnitude and distribution of cypermethrin from total release, over-the-counter foggers was studied in a test room and in residences to facilitate evaluation of regulatory exposure algorithms and new human exposure assessments based upon urine biomonitoring. Surface residue (SR) was evenly distributed in a small test room (3.6 mciro g cypermethrin/cm(2)) where thorough mixing of the aerosol occurred. In a residence SR was significantly affected by room size and distance from the fogger. Air levels in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…48 b Keenan et al 52 and Williams et al 53 c Eadsforth et al, 24 Hughes et al, 41 Reifenrath et al, 42 Tomalik-Scharte et al 28 and Woolen et al 27 d Estimated based on the assumption that one fingertip area is ~30% of one finger area, and each finger area is ~10% of the palmar surface of one hand. The average surface area of hands for adult male and female is 0.098 m 2 .…”
Section: Figurementioning
confidence: 99%
“…48 b Keenan et al 52 and Williams et al 53 c Eadsforth et al, 24 Hughes et al, 41 Reifenrath et al, 42 Tomalik-Scharte et al 28 and Woolen et al 27 d Estimated based on the assumption that one fingertip area is ~30% of one finger area, and each finger area is ~10% of the palmar surface of one hand. The average surface area of hands for adult male and female is 0.098 m 2 .…”
Section: Figurementioning
confidence: 99%
“…A recent model evaluation effort (Young and Driver, 2008;Young et al, 2012) summarized biomonitoring results from Keenan (2007) and Keenan et al (2009), and concluded that exposure from broadcast applications (i.e., foggers) appears to be predicted accurately by the models; however, exposure predictions from localized applications such as C&C are two orders of magnitude higher than biomonitoring results. Thus, it was apparent that refinement of algorithms and models for C&C scenarios need to be developed to account for contact probability.…”
Section: Discussionmentioning
confidence: 94%
“…The reaction mixture contained: 0.05 M phosphate buffer, 5 mM EDTA, pH 7.0, 0.125 M NaN 3 , 0.0084 M NADPH, 0.15 M glutathione (GSH), 7.6 Units of glutathione reductase (E.C.1.6.4.2,) 0.0022 M hydrogen peroxide and 30 /-11 of normalized samples pretreated with Drabkin's reagent. GPx catalyses the oxidation of GSH by hydroperoxide.…”
Section: Glutathione Peroxidase Activitymentioning
confidence: 99%
“…Symptoms of CY toxicity in laboratory animals include pawing, burrowing, salivation, tremors, writhing, and seizures. In humans, high doses of CY result in twitching, drowsiness, coma, and seizures (2,3). In addition to neurons, reproductive organs are another toxic target ofCY (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation